Factors Affecting Community Participation In The Doyo Lama And Tobati Tourism Villages - Kadun MT, Alienra Davry Nanda; Nurjaman, Rahmat (Universitas 17 Agustus 1945 Surabaya, 2024)
The practice of tourism villages in Indonesia applies the principle of Community Based Tourism. This study occurred in Tobati and Doyo Lama tourist villages in Jayapura, Papua. Notably, these two villages won the Indonesian Tourism Village Award in 2022. The purpose of this study is to describe community participation in tourism management in Jayapura. In general, tourism in Papua is located on customary land; therefore, its management is dominated by customary structures. Researchers want to provide a complete picture of the factors influencing community participation. The study aimed to examine the influence of the variables of economic benefits (X1), tourism resources (X2), social capital (X3), community influence (X4), and mechanisms and policies (X5) on community participation (Y). The study refers to instruments tested by Mai et al.. Using a multiple linear regression model, the researcher wanted to demonstrate the simultaneous and partial influence of variable X. The results of the study showed a significant simultaneous influence of the five factors (X1, X2, X3, X4, X5) on participation (Y). However, different partial influences were found in the two villages. In Tobati, tourism resources were the only variable that had a significant influence, while in Doyo Lama, tourism resources, social capital, and community influence significantly influenced participation. The findings at both sites showed variables with no influence, variables with a positive influence, and variables with a negative influence. Tourism managers in Tobati and Doyo Lama villages need to pay attention to the participation aspect in managing their tourism.